INSURANCE LITERACY AS A CATALYST FOR COMMUNITY EMPOWERMENT AND FINANCIAL INCLUSION - Nurhayati; Wijaya, Richy; Esya, Lavlimatria; Wijayanto, Rakendro; Laksmi Subadra, Ni Putu Ayu (Jurnal Pengabdian Masyarakat Sabangka, 2025)
The Community Service Program (PkM) by Trisakti University, titled "Insurance Literacy as an Educational Tool to Raise Insurance Awareness," took place in Kadumanggu Village, Babakan Madang, Bogor. The initiative aimed to enhance public understanding of insurance as a means of managing financial risks. Activities involved 28 participants from diverse backgrounds and included interactive presentations, discussions, and case-based simulations. Program effectiveness was measured through pre- and post-training assessments, analyzed using the Kolmogorov–Smirnov test and paired samples t-test. Findings revealed a statistically significant improvement in insurance literacy (sig = 0.000 < 0.05), highlighting the program's effectiveness. Participants also showed more openness and confidence regarding insurance. Contributing factors included participant enthusiasm, facilitator competence, and relevant materials. However, challenges included limited facilities and participant diversity. Output included higher literacy scores, a training module, and a participant database for future research. The program recommends wider replication, industry collaboration, and digital platforms for broader outreach.